Daya Guna dalam Pelaksanaan Program Pembangunan Jembatan Tunggulmas untuk Menanggulangi Kemacetan di Kota Malang - Indahwati, Baretha; Hayat, Hayat; Rahman Ilyas, Taufiq (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2024)
Every human activity, whether ordinary work activities, business, education, social activities, and so on, depends on the transportation sector. Considering that transportation is the result of the movement of people and objects, improving the transportation system requires comprehensive handling. This has resulted in the growth rate of urbanization flows from rural to urban areas being quite high. For example, the population of Malang City has increased in the last eight years, from 804,803 people in 2013 to 844,933 people in 2021. Public problems have also emerged, starting from the loss of green space, changes in urban planning design, to the phenomenon of traffic jams. This research uses a descriptive method with qualitative data analysis, namely a problem solving approach that seeks the best way to characterize the current state of the research object based on available facts. It is natural that Malang City, which is the second largest city in East Java, cannot be separated from the population explosion. From many angles, this causes traffic jams, which can impact the ability of these neighborhoods to carry out daily activities comfortably, safely and peacefully. After the construction and inauguration of the TUGGULMAS Bridge on February 24 2022, one of the traffic hotspots is on Jalan Raya Tlogomas. The discussion above shows that there is still room for improvement in the implementation of the TUGGULMAS Bridge construction program to ease traffic congestion in Malang City. seen from the various ways of implementing and monitoring the WTulmas Bridge Construction Program, from the way the Program is evaluated and influenced, and from the way the Program is supported and inhibited effectively and efficiently to achieve these goals. reduce traffic jams in Malang City